Pengaruh Brand Positioning dan Brand Equity terhadap Keputusan Pembelian Burger Bangor Kandangan - M. Salahuddin; Saladin Ghalib (JURNAL BISNIS DAN PEMBANGUNAN, 2025)
Abstract: One of the fast food restaurants which is a local Indonesian product is Burger Bangor which is the people's burger choice. This research shows the influence of brand positioning and brand equity on purchasing decisions for the Bangor Kandangan Burger.The research location chosen was Burger Bangor Kandangan. The total sample used was 80 respondents. A questionnaire was chosen as a research instrument to collect data and multiple linear regression analysis was used for hypothesis testing. This research results show that brand positioning has a significant effect on consumer purchasing decisions. Brand equity has a significant influence on consumer purchasing decisions. Brand Positioning and Brand Equity have a significant influence simultaneously on purchasing decisions for the Bangor Kandangan Burger